COMPARISON OF THE EFFECTIVENESS OF LAVENDER AROMATHERAPY AND PROGRESSIVE RELAXATION TECHNIQUES ON THE SLEEP QUALITY OF PREGNANT WOMEN IN THE THIRD TRIMESTER AT THE KARANGPAWITAN PUBLIC HEALTH CENTER, GARUT REGENCY IN 2025 - Puji Sri Fauzi; Agustina Sari (Universitas Dharmawangsa Medan, 2026)
According to the World Health Organization (WHO), the number of dysmenorrhea cases in 2020 was 1,769,425 individuals, with 90% being female. The prevalence of dysmenorrhea in Indonesia is 54.89% for primary dysmenorrhea and 9.36% for secondary dysmenorrhea. In DKI Jakarta, the prevalence of primary dysmenorrhea is 87.5%. Menstrual pain, also known as dysmenorrhea, occurs due to dysrhythmic contractions of the myometrium. The pain often interferes with daily activities, making its impact on adolescent girls particularly significant. The aim of this study is to determine the effect of green coconut water and effleurage massage on reducing the intensity of primary dysmenorrhea pain in adolescent girls at Dewi Medika Primary Clinic in 2025. This research uses a qualitative method with a case study approach. The sample consisted of two respondents experiencing primary dysmenorrhea, comparing one who received green coconut water and the other who received effleurage massage. The study was conducted in February 2025. The results showed a reduction in pain intensity in adolescents who experienced primary dysmenorrhea after receiving either green coconut water or effleurage massage. The decrease in pain intensity was more effective and occurred more quickly in the adolescent who received the effleurage massage compared to the one who received green coconut water.